Arbitration practice in Zambia : the process and its legal impediments - Sianondo, Clavel (Department of Commercial Law, 2016)
Arbitration as a process of dispute resolution has been pivotal in addressing a lot of business needs to have the dispute resolved within a short period and with less inconveniences to their business. The principle of confidentiality gives impetus to the process. The skill of the arbitrators and the general party autonomy has made the process and awards to be fully complied. Despite the monumental progress made in the field of arbitration as a means of dispute settlement, the process has been beset by reversal which is inherent in the Arbitration Act itself thereby whittling down the advantages ascribed to the process. To this end, the study therefore highlights the historical development of arbitration in Zambia. The process of arbitration and its role in enhancing access to justice will also be examined. The advantages and how the same have been weakened by the Arbitration Act, other legislations and indeed the interpretive impositions by the court will be investigated. Among other provisions which fly in the teeth of the entire process is its usually unqualified attachment to the court system without cognisance of the aspiration of the entire process of arbitration. To redress these weaknesses in the Act and the rules which guide the arbitration process, this study will spur reforms so as to bring the law into conformity with the expectations of the end users.